Examining charter school policy and public school district resource allocation in Ohio - Matthew Allen Linick (Arizona State University, 2016)
This project focuses on the competitive pressure, or the threat of competitive pressure, generated by charter school policy. This paper uses longitudinal district-level data and multiple quasi-experimental designs to examine the relationship between two Ohio charter school policies and changes in public school district instructional resource allocation. Some believe that the competitive pressure created by charter schools will improve efficiency in district-run public schools; however, the findings from this study do not reliably demonstrate that charter school policy will induce a public school district to increase the level of instructional resource allocation. The findings do provide evidence that some charter policies are linked to changes in resource allocation at certain school districts. This study suggests that additional, multiple method investigations are needed to study how public school districts respond to competition and policies designed to change the levels of competition in the public school system.